Detection of Aflatoxins and Proximate Analysis of Selected Different Processed Foods: Biscuits, Cakes and Noodles from Lahore, Pakistan: Detection of Aflatoxins in Foods - Yumna Sadaf; Naseem Zahra; Muhammad Khalid Saeed; Rida Mohsin; Sajid Rashid Ahmad (Biological Sciences - PJSIR, 2023)
The current study was conducted to assure quality of biscuits, cakes and noodles by determining aflatoxin B1 and proximate composition of the selected food products. A total of 60 samples (20 each of biscuits, cakes and noodles) were collected from diverse areas of Lahore. Aflatoxins were determined using thin layer chromatography by adopting standard method of the association of official analytical chemists (AOAC). The proximate composition was also determined for selective products. Different parameters like moisture, ash content, crude fiber, crude protein and crude fat in percentages were deter- mined in selected food products. The correlation of aflatoxins was calculated with each factor at significant level (P<0.05). Total 19 samples (32.0%) showed presence of aflatoxins. Aflatoxins contamination was observed in 10%, 8.3% and 13.3% contamination in biscuit, cakes and noodles respectively and 89.4% of the total contaminated samples were within permissible limits, while 10.6% (2 samples) were contaminated beyond permissible limits. In cakes, highest moisture content (9.54-19.47%) was observed. Moisture content was 2.23-6.71% in biscuits and 1.21-3.79% in noodles. The minimum and maximum value of ash, crude fiber, crude fat and crude protein were 1.09-2.37%, 0-1.21%, 0.53-9.92% and 2.01-3.91% corres- pondingly in noodles. The range of ash contents, fiber contents, fat contents, protein contents in cakes 1.12-1.68%, 0-0.97%, 19.76-27.21%, 4.10-5.81%, respectively. In biscuits ash content, crude fibre, fat contents and protein contents range is 0.87-2.98%, 0-1.31%, 19.12-27.45%, 7.02-9.49%, respectively. Positive correlation (r=0.459) was found between aflatoxin contamination and moisture contents in cakes. It is needed to monitor aflatoxins levels in processed food due to increase in its occurrence day by day.